Efeito da quantidade finita de osciladores em sistemas estocásticos de dois níveis - Pinto, Italo ivo Lima Dias (2014)
In this thesis, we presented models of two state stochastic systems which interact through a global coupling, in a way that each population unit contributes to the state transition rates of the other units. We presented two models of global coupling in which is possible to observe a phase transition of a regime with units equally distributed on the two states to a phase where there is an agglomeration of units in one of the states. In the first coupling model this transition occurs in a continuous way as we increase the coupling parameter. Through a mean field approximation we shown that this phase transition occurs due to a subcritical pitchfork bifurcation where one of the phases is associated to a monostable regime (units equally distributed in the two states) and the other phase to a symmetric bistable regime (majority of the units agglomerated in one of the states). On the other hand the other model presents a discontinuous phase transition as we increase the coupling parameter, the mean field approach shows that this phase transition occurs due a supercritical pitchfork bifurcation where we have a monostable regime and a tristable regime presenting symmetry in relation to the central potential well, as the coupling parameter is increased the central stability reduces while the two other states becomes more stable. It was shown that for both coupling models, when we have a finite number of oscillators the system presents a multiplicative noise structure. This noise structure turns the stable states obtained with the mean field approximation on metastable states, also the fluctuations due to a finite number of units breaks the symmetry in the multistable regimes, this symmetry break occurs due to the asymmetric intensity of the fluctuations. We also obtained a Fokker-Planck equation for this system and the probability distribution of the number of units in each state, from this distribution it was possible to build a phase diagram for the phase transition from themonostable regime to the regime that presents multistability. This transition is characterized in terms of the coupling parameter and the number of units in the system.